Bonaventūra Gailevičius – tikėtinas 1805 m. Išguldymo afieros mišių šventų ir 1806 m. Lietuviškų evangelijų autorius - Subačius, Giedrius (Baltistica, 1998)
BONAVENTURA GAILEVIČIUS – THE PROBABLE AUTHOR OF ‘AN EXPLANATION FOR THE CELEBRATION OF SACRED MASS’ (1805) AND ‘THE LITHUANIAN GOSPELS’ (1806)In this article I am forced to conclude that two Lithuanian religious books of the very beginning of the nineteenth century (Išguldymas Afieros Mišių Šventų, 1805 [IAMS1805] ‘An Explanation for the Celebration of Sacred Mass’ and Lietuviškos Evangelijos, 1806 [LEX 806] ‘Lithuanian Gospels’) were written by the same principal author/editor. The following statements serve as a proof: 1 ) both books are written by a Lowlander, 2) both books encompass ample traces of conscious efforts to change native Lowland dialect into the Highland one, 3) most of the Highland dialect features are the same in both books (all of the four usually noticeable Lowland dialect forms and three out of six occasionally noticeable: 3 praes., dat. pl., loc. pl. -ūse), 4) there are analogous errors of dialectal interference; i. e. forms produced by erroneous phonetic or morphological reconstruction (cf.IAMS1805 neys ‘nes’, widuoje ‘viduje’,apsileydimo ‘apsileidimą’ and LEl806 neys ‘nes’,wirszuoje ‘viršuje’, wardo ‘vardą’ etc.). It is almost inevitable that the principal author/editor of both books must have been the same person.Historical sources have not been of much help in establishing authorship as traditionally they have been contradictory. They point out the following probable authors/editors of either one or the other book: Silvestras Rucevičius, Dominykas Mogenis, Bonaventūra Gailevičius. Although Rucevičius was also a Lowlander his habitual linguistic usage permits me to negate his authorship: Rucevičius switched to the Highland dialect forms to much lesser degree than the author/editor of IAMS1805 and LEl806. His frequent erroneously reconstructed Highland forms are of very different type as well (cf. prieliginima ‘prilyginimą’, nuoweste ‘nuvesti’).There is no single Lithuanian text extant which we could positively identify as being by Mogenis. The geographical area of his surname, Mogenis, does not border on territory where the Lowland dialect is spoken. Mogenis attended Kaunas High School which is remote from the Lowlands. Thus hypothetically I dare to assume that Mogenis was not a native Lowlander and consequently could not have produced the IAMS1805 and LEl806 texts.A comparison of IAMS1805 and LEl806 with the original Gailevičius texts proves that most linguistic forms in them are consistently analogous. Some Highland dialect features are slightly more frequent in original Gailevičius texts than they are in IAMS1805and LEl806. However, this difference can be explained by the long gap in time – the text of Gailevičius is a much later one. During that period Gailevičius could have learned more Highland dialect forms and used them, motivated by his desire to write in Highland Lithuanian. So we possess no convincing arguments to deny Bonaventūra Gailevičius’ authorship of the IAMS1805 and LEl806 texts.